2018
DOI: 10.1038/s41598-018-33295-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of NiAl2O4-Based Flexible Substrates for Metamaterials with Negative Dielectric Properties

Abstract: Various techniques are commonly used to produce nano-crystalline NiAl2O4 materials; however, their practical applications in the microwave region remain very limited. In this work, flexible substrates for metamaterials containing two different concentrations of NiAl2O4 (labelled Ni36 and Ni42) have been synthesised using a sol-gel method. The formation of spinel structures in the synthesised materials is confirmed, and their crystalline sizes are determined using scanning electron microscopy, X-ray diffraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 38 publications
1
12
1
Order By: Relevance
“…The first reports of such rare dielectric behavior in the real material were presented Mao et al [ 36 , 37 ]. In recent years, more and more papers present the occurrence of this phenomenon in various ceramic materials [ 38 , 39 , 40 ], but so far, the mechanism of the appearance of a negative dielectric constant is not yet fully examined and explained. Mao et al [ 36 ] reported that the negative value of the dielectric constant is related to the change in the nature of the electrical conductivity from capacitive to inductive.…”
Section: Resultsmentioning
confidence: 99%
“…The first reports of such rare dielectric behavior in the real material were presented Mao et al [ 36 , 37 ]. In recent years, more and more papers present the occurrence of this phenomenon in various ceramic materials [ 38 , 39 , 40 ], but so far, the mechanism of the appearance of a negative dielectric constant is not yet fully examined and explained. Mao et al [ 36 ] reported that the negative value of the dielectric constant is related to the change in the nature of the electrical conductivity from capacitive to inductive.…”
Section: Resultsmentioning
confidence: 99%
“…Another challenge of designing flexible antennas is identifying suitable conducting materials that sustain different bending and twisting conditions and have reasonable resistance value as not to affect the antenna radiation efficiency. Various methods have been considered to find the conductive substrates, such as chemically modifying fabrics surface [ 252 ] or physical mixing of several conductive materials [ 253 , 254 , 255 ].…”
Section: Challenges and Future Prospects Of Flexible Antennasmentioning
confidence: 99%
“…The sol-gel method is used to manufacture the final substrate [18]. Figure 3 presents a flow chart of the synthesis steps of nickel aluminate powder by the sol-gel method.…”
Section: Preparation Of Flexible Nickel Aluminate (Nial2o4)mentioning
confidence: 99%
“…The sol-gel method is used to manufacture the final substrate [18]. Table 2 shows the relative molecular mass (JMR) and the volume of solvent and other materials used to produce solutions for calculation purposes.…”
Section: Preparation Of Flexible Nickel Aluminate (Nial 2 O 4 )mentioning
confidence: 99%